Studies on analgesic, antipyretic and anti-inflammatory activities of methanol extract of kaempferia galanga L. in experimental animals - Chutha Sae-Wong (Prince of Songkla University, 2007)
Thesis (M.Sc., Pharmacology)--Prince of Songkla University, 2007